Evaluation of Penicillin Binding Protein 2a (PBP-2a) Latex Agglutination Assay for Rapid Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) Isolated from Blood Culture Growth - Bushra, Riffat; Naqvi, Sakeenah Hussain; Mirza, Irfan Ali; Imtiaz, Anam; Sajjad, Rabia; Gill, Maria Mushtaq (Pakistan Armed Forces Medical Journal, 2024)
• Objective: To determine in vitro activity of Penicillin Binding Protein 2a Latex Agglutination Assay for Rapid Identification of Methicillin-Resistant Staphylococcus aureus isolated from positive blood culture growths.Study Design: Cross-sectional study.Place and Duration of Study: Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, Jan to Jun 2022.Methodology: Staphylococcus aureus isolates were taken from a subculture of blood culture samples flagged positive by the BactAlert automated blood culture system. A total of 107 isolates were included in the study. A latex agglutination assay was used to identify Methicillin-Resistant Staphylococcus aureus and non-Methicillin-Resistant Staphylococcus aureus isolates. The Cefoxitin disc diffusion test also tested the isolates, keeping it the reference method.Results: Out of 107 samples, 92 isolates were identified as Methicillin-Resistant Staphylococcus aureus by latex agglutination and Cefoxitin disc diffusion. The rest of the isolates were identified as Methicillin-Susceptible Staphylococcus aureus.Conclusion: The latex agglutination assay is a highly sensitive, cost-effective, less time-consuming, and accurate test that may be used in routine laboratories for rapid identification of staphylococcus aureus isolates as Methicillin-Resistant Staphylococcus aureus.